Urban Tree diversity and DBH in Batu Kawah New Township - Adeline, Edwin Amin Takong (Universiti Malaysia Sarawak (UNIMAS), 2013)
Street trees are an important component of the urban forest as they provide critical ecosystem services which contribute to human health and environmental quality. Urban trees and forest are considered integral to the sustainability of a city. Yet, sustainable urban forest are not born but made through community-wide commitment on their creation and management. However, due to rapid urbanization and land conversion, most greenery spaces both within and around urban area has slowly diminished.